Semantic Metadata as Meaning Making: Examining #hashtags and Collection Level Metadata - White, Hollie; Gibbons, Leisa (Dublin Core Metadata Initiative, 2019)
Memory institutions and other organizations interested in preserving social media data are using a variety of collection level metadata to represent those materials. The aim of this paper is to start a dialogue within the metadata community about how metadata professionals can describe social media collections in better ways to ensure that the semantic complexity of hashtags remain intact at the collection level. This paper explores how hashtags manifest semantic metadata and how that expression is formally described. A study was conducted using two datasets. The first dataset on hashtags as defined by professional literature was examined and categorized using thematic analysis. The second dataset collected metadata from a selection of Document the Now Twitter datasets and was categorized using Gilliland’s (2016) five categories of metadata. Findings delve into the use of collection level metadata to describe social media content.